Pemberdayaan Kesehatan dan Ekonomi Masyarakat Melalui Pemanfaatan Tanaman Obat Keluarga: Empowerment of Community Health and Economy Through the Use of Family Medicinal Plants - Faradila Faradila; Nurul Qamariah; Rika Arfiana Safitri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Family Medicinal Plants (TOGA) have significant potential to support household health self-reliance and improve family income; however, their utilization at the community level is often limited to traditional use without value-added processing. This community engagement program aimed to strengthen the health and economic capacity of women’s religious study groups in Kalampangan through education, cultivation training, and processing of TOGA into herbal products. The program was implemented using a participatory approach through counseling sessions, hands-on training, and continuous assistance. Evaluation was conducted using pre–post tests on TOGA utilization and cultivation, with qualitative analysis into low, moderate, and high categories, supported by field observations and product evaluation. The results showed a clear shift in participants’ understanding from low to moderate and high categories across most indicators. In addition, participants successfully produced four herbal products, namely herbal tea bags, ginger-based herbal drinks (gingershoot), turmeric-based herbal drinks (curcuminshoot), and aromatic candles, and established a Joint Business Group to support program sustainability. These findings indicate that community-based utilization of family medicinal plants is not only effective in improving household health awareness but also has strong potential as a sustainable community-based economic empowerment strategy.